Non-Radioactive Source for Field Applications Based in a Plasma Focus of 2j Pinch Evidence - Pedreros, J (Institute of Physics Publishing, 2014)
A portable plasma focus for field applications operating at two joules have been designed and constructed. Pinch evidence in the current derivative signal have been obtained. Also the dependence of the time to pinch, tp, over the filling pressure, p0, (tp ? =p0) was observed. Therefore, the device is working as a plasma focus.